Digital Transformation: Impact of Information Technology Management at Pondok Pesantren Ihyaul Ulum - Muhammad, Muhammad; Humaidi, Anis; Maghfiroh, Lailatul (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2025)
The digitalization of Islamic boarding schools (pesantren) has become a strategic step in addressing the development of information technology. Ihyaul Ulum Islamic Boarding School is one example of an Islamic boarding school that has adopted digital systems in various aspects, including administration, education, and preaching. This study aims to analyze the impact of digitalization in Islamic boarding schools, focusing on the application of information technology, the benefits for students and administrators, and the challenges faced in implementing digitalization. The results show that digitalization offers various benefits, such as increased administrative efficiency, easier access to information, financial transparency, and a modernized learning system. However, challenges such as limited infrastructure, data security, and the potential for misuse of technology remain major concerns. With a wise approach, digitalization can improve the quality of education in Islamic boarding schools without sacrificing the traditional values that are the foundation of these institutions.